Penentuan Umur Simpan Dodol Nangka dengan Metode ESS (Extended Storage Studies) - Siti Muizzun Nisak; Ida Bagus Putu Gunadnya; I Made Anom S. Wijaya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2014)
The objective of this research was to know the shelf life of jackfruit dodol that estimated by using ESS (Extended Storage Studies) methode. The ESS method was obtained by organoleptics test and determined at over range of the room temperature 28-30ºC with relative humidity of the storage room is 75%, the criterias of organoleptics test were texture, aroma, and colour. The other parameters estimated during organoleptics test were the weight and the moisture content change of jackfruit dodol. The result showed that the taste of jackfruit dodol was accepted at 4.2 for the elasticity, 4.8 for the aroma and the colour. Organoleptic test was stopped when the panel refused to do test for mold growth on the surface of jackfruit dodol. The shelf life of jackfruit dodol was 113 days.